Предмет: Математика,
автор: 600700090
(х-3)(х+1)=(5х-4)(х+1)
Ответы
Автор ответа:
0
( х - 3 )•( х + 1 ) = ( 5х - 4 )•( х + 1 )
Х^2 + х - 3х - 3 = 5х^2 + 5х - 4х - 4
Х^2 - 2х - 3 = 5х^2 + х - 4
4х^2 + 3х - 1 = 0
D = 9 + 16 = 25 ; V D = 5
X1 = ( - 3 + 5 ) : 8 = 0,25
X2 = ( - 3 - 5 ) : 8 = - 1
Ответ 0,25 ; - 1
Х^2 + х - 3х - 3 = 5х^2 + 5х - 4х - 4
Х^2 - 2х - 3 = 5х^2 + х - 4
4х^2 + 3х - 1 = 0
D = 9 + 16 = 25 ; V D = 5
X1 = ( - 3 + 5 ) : 8 = 0,25
X2 = ( - 3 - 5 ) : 8 = - 1
Ответ 0,25 ; - 1
Похожие вопросы
Предмет: Математика,
автор: sofakoroleva29
Предмет: Физика,
автор: diana8869
Предмет: Русский язык,
автор: soyouagain20
Предмет: Обществознание,
автор: дияныч
Предмет: Математика,
автор: vasilekdeg52